2015
DOI: 10.1681/asn.2014111141
|View full text |Cite
|
Sign up to set email alerts
|

The Janus Faces of IL-6 in GN

Abstract: various miR, and miR-21 is one of the most intensively studied miR regulated by HIF-1. 11 The complex network of HIF-1 and miR is a critical subject for future studies.PTEN is also known to be involved in a network of interactions with p53, which transcriptionally activates genes involved in cell cycle control and apoptosis. PTEN regulates p53 protein levels and transcriptional activity through both phosphatase dependent and independent mechanisms. A crucial role of p53 in tubules damaged by ischemia reperfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The effect of IL-6 blockade on this murine cGN model remains controversial. 20,25,26 In our model, an Il-6 À/À background reduced disease severity (Supplementary figure 4a and b). Furthermore, anti-IL-6R antibody (MR16-1) treatment at the early phase ameliorated pathological results (Supplementary figure 5a and b).…”
Section: Il-6 Blockade Enhanced Treg Accumulation and M2-like Type Mamentioning
confidence: 68%
See 1 more Smart Citation
“…The effect of IL-6 blockade on this murine cGN model remains controversial. 20,25,26 In our model, an Il-6 À/À background reduced disease severity (Supplementary figure 4a and b). Furthermore, anti-IL-6R antibody (MR16-1) treatment at the early phase ameliorated pathological results (Supplementary figure 5a and b).…”
Section: Il-6 Blockade Enhanced Treg Accumulation and M2-like Type Mamentioning
confidence: 68%
“…The effect of IL‐6 blockade on this murine cGN model remains controversial 20,25,26 . In our model, an Il‐6 −/− background reduced disease severity (Supplementary figure 4a and b).…”
Section: Resultsmentioning
confidence: 87%
“…Macrophage activation and polarization are also found to be correlated with IL-6 and its receptor. M1 macrophages are responsible for amplifying the inflammatory feedback loop whereas M2 macrophages are anti-inflammatory and therefore critical to establishing metabolic control and tissue homeostasis [29] , [30] . Studies have shown that blockade of IL-6R function positively correlates with activation of M1 macrophages as well as with IL-6 trans-signaling-mediated pro-inflammatory responses.…”
Section: Explaining Cytokine Storm and Associated Complications In Comentioning
confidence: 99%